Antimicrobial Activity of Mesenchymal Stem Cells: Current Status and New Perspectives of Antimicrobial Peptide-Based Therapies - Alcayaga-Miranda, Francisca; Cuenca, Jimena; Khoury, Maroun (Frontiers in Immunology, 2017)
While mesenchymal stem cells (MSCs)-based therapy appears to be promising, there are concerns regarding possible side effects related to the unwanted suppression of antimicrobial immunity leading to an increased risk of infection. Conversely, recent data show that MSCs exert strong antimicrobial effects through indirect and direct mechanisms, partially mediated by the secretion of antimicrobial peptides and proteins (AMPs). In fact, MSCs have been reported to increase bacterial clearance in pre-clinical models of sepsis, acute respiratory distress syndrome and cystic fibrosis related infections. This article reviews the current evidence regarding the direct antimicrobial effector function of MSCs, focusing mainly on the role of MSCs-derived AMPs. The strategies that might modulate the expression and secretion of these AMPs, leading to enhanced antimicrobial effect are highlighted. Furthermore, studies evaluating the presence of AMPs in the cargo of extracellular vesicles (EVs) are underlined as perspective opportunities to develop new drug delivery tools. The antimicrobial potential of MSCs-derived EVs can also be heightened through cell conditioning and/or drug loading. Finally, improving the pharmacokinetics and delivery, in addition to deciphering the multi-target drug status of AMPs, should synergistically lead to key advances against infections caused by drug resistant strains.